Cognitive behavioural anger management intervention for people with intellectual disabilities: costs of intervention and impact on health and social care resource use. (9th January 2014) - Felce, D.; Cohen, D.; Willner, P.; Rose, J.; Kroese, B.; Rose, N.; Shead, J.; Jahoda, A.; MacMahon, P.; Lammie, C.; Stimpson, A.; Woodgate, C.; et al.
Abstract Background Anger and aggression among adults with intellectual disability (ID) are associated with a range of adverse consequences for their well‐being and that of their family or staff carers. The aims were to evaluate the effectiveness of an anger management intervention for adults with mild to moderate ID and to evaluate the costs of the intervention and its impact on health and social care resource use. This paper is concerned with the latter aim. Methods A cluster‐randomised controlled trial was conducted involving day services for adults with ID in Scotland, England and Wales. Incremental costs of delivering the intervention and its impact on subsequent total health and social care package costs were calculated. Full data comparing costs between baseline and follow‐up 10 months later were collected for 67 participants in the intervention arm and 62 participants in the control arm. Cost differences between the groups at follow‐up, adjusted for baseline levels, were calculated using non‐parametric bootstrapping controlling for clustering. Results The mean hourly excess cost of intervention over treatment as usual was £12.34. A mean adjusted cost difference of £22.46 per person per week in favour of the intervention group was found but this was not statistically significant. Conclusions The baseline‐adjusted cost difference at follow‐up would result in a fairly immediate compensation for the excess costs of intervention, provided the difference is not a statistical artefact. Further research is needed to clarify the extent to which it might represent a real saving in service support costs.